Productivity Expansion in Massimo Bakery - Islam, Shekh Md. Samiul; Abdillahi, Badri Ali; Mohamud Nour, Ahmed Yasin (IIUM Journal of Case Studies in Management, 2019)
In today’s competitive world, it is important to improve constantly for both manufacturing and service industries. Quantity with quality is a main characteristic which helps a company to stay in the competition. Technology has been taken leaps of development lately and this has brought an escalation in the customer demands. Bakery products become a regular food in most parts of the world and are essential commodities today. There is a high potential for business growth in selling bakery products. The case study deals with the issues faced by bakery industry and provided some recommendations to resolve the existing problems in the bakery. The main aim is to study the current productivity and capacity of the plant, analyse it to find areas of improvement and make an improvement proposal to meet the forecasted increase in demand. In the workstation, the processing time is different and the longest time consumption is identified as a bottleneck. The identified bottleneck station is analysed to reduce the processing time which increases production rate.